2021
DOI: 10.11606/issn.1678-4456.bjvras.2021.172805
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Salmonella spp. in raw milk from dairy herds in Colombia

Abstract: Salmonellosis is a foodborne disease (FBD) that affects public health and can cause death in people. Many outbreaks of Salmonellosis have been reported due to the contamination of raw milk and dairy products with the pathogen. To determine the prevalence of Salmonella spp. in milk samples from four dairy herds in the Sabana of Bogotá in 2017, 112 milk samples were taken directly from the mammary gland during milking. All milk samples were cultured and tested to isolate and identify Salmonella spp. using microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
4
1
Order By: Relevance
“…Also, lower occurrence was observed by[21] who isolated NTS from 3% (4 out of 133) of raw market milk samples but they failed to isolate Salmonella from milk samples collected directly from teat of lactating cows. On the other hand,[22] estimated higher occurrence (20.5%) of NTS in raw milk collected directly from the mammary gland during milking than in our study. Omar, et al[23] illustrated that high presence of Salmonella among raw milk may be attributed to shedding of Salmonella into milk from the infected udder or contamination of raw milk with feces during its collection.…”
contrasting
confidence: 84%
“…Also, lower occurrence was observed by[21] who isolated NTS from 3% (4 out of 133) of raw market milk samples but they failed to isolate Salmonella from milk samples collected directly from teat of lactating cows. On the other hand,[22] estimated higher occurrence (20.5%) of NTS in raw milk collected directly from the mammary gland during milking than in our study. Omar, et al[23] illustrated that high presence of Salmonella among raw milk may be attributed to shedding of Salmonella into milk from the infected udder or contamination of raw milk with feces during its collection.…”
contrasting
confidence: 84%
“…However, a previous study in Ethiopia demonstrated that the most common serovar were S. dublin and S. Virchow [ 21 ]. Additionally, S. newport and S. typhimurium were the most predominant in Colombia by (60.87%) and (17.4%) respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella spp. may be excreted directly in the milk by an infected animal [103]. E. coli is a normal inhabitant of the intestines of animals and humans but its recovery from food may be of public health concern due to the possible presence of enteropathogenic and/or toxigenic strains which lead to sever gastrointestinal disturbance [104].…”
Section: Public Health Importance These Of Mastitis Causing Pathogensmentioning
confidence: 99%